Biostratigraphy and isotope stratigraphy of upper Maastrichtian–Danian marine deposits of the Kopet-Dagh Basin, northeast Iran. (October 2018) - Ezampanah, Yadolah; Scopelliti, Giovanna; Sadeghi, Abbas; Jamali, Amir Mohammad; Yazdi-Moghadam, Mohsen; Kamyabi Shadan, Hossein
Abstract: Biostratigraphy, using foraminifera and echinoids, plus high-resolution carbon isotope stratigraphy of the upper Maastrichtian–Danian interval in the western part of the Kopet-Dagh Basin in northeast Iran are outlined. Our study of shallow-marine carbonate platform deposits of the Kalat Formation, rich in larger benthic foraminifera (predominantly Clypeorbis mammillatus Schlumberger, Lepidorbitoides sp. and Siderolites calcitrapoides Lamarck), has allowed the definition of a C . mammillatus - S . calcitrapoides Assemblage Zone, of late Maastrichtian age. Clypeorbis mammillatus is here recorded for the first time from the Maastrichtian Kalat Formation and represents the most easterly find of this taxon in the European faunal province. From Danian strata of the Chehel Kaman Formation three genera ( Cyclaster, Echinocorys and Pseudogibbaster ) and four species of echinoids were identified. In addition, three planktonic foraminiferal biozones are introduced here for the Danian interval of the Chehel Kaman Formation studied, i.e., Guembelitria cretacea Zone, Eoglobigerina eobulloides – Subbotina triloculinoides Interval Zone (Pα-P1a) and Subbotina triloculinoides Subzone (P1b). The isotope profile obtained correlates with the subtropical Bottaccione/Contessa reference curve for the K/Pg boundary interval and, on a regional scale, with the Maraveh Tapeh section, which represents the δ 13 C positive excursion of KPg-2 and the upper negative excursion of the KPg-3. The K/Pg boundary, placed at the δ 13 C maximum above KPg-3, corresponds in the Qareh Galdy section with sample 2239. Highlights: We extend the palaeobiogeographic bioprovince extension of Clypeorbis mammillatus eastwards as far as NE Iran. First isotope stratigraphy of the upper cretaceous and Danian deposits in the west Kopet-Dagh Basin. This section represents the δ 13 C positive excursion of KPg-2 and the upper negative excursion of the KPg-3.